2019
DOI: 10.3390/v11070644
|View full text |Cite
|
Sign up to set email alerts
|

A Lineage of Begomoviruses Encode Rep and AC4 Proteins of Enigmatic Ancestry: Hints on the Evolution of Geminiviruses in the New World

Abstract: The begomoviruses (BGVs) are plant pathogens that evolved in the Old World during the Cretaceous and arrived to the New World (NW) in the Cenozoic era. A subgroup of NW BGVs, the “Squash leaf curl virus (SLCV) lineage” (S-Lin), includes viruses with unique characteristics. To get clues on the evolutionary origin of this lineage, a search for divergent members was undertaken. Four novel BGVs were characterized, including one that is basal to the group. Comparative analyses led to discover a ~670 bp genome modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…All the proteins have the average size of BGVs proteins, with the exception of AC4. The AC4 protein is 130 aa in length, which is unusually long since the average size of AC4 protein is~85 aa for typical BGVs and 121 aa in length for BGVs belonging to SLCuV clade (Torres-Herrera et al, 2019). A BLASTP search revealed that only CuChLV and another three BGVs of the SLCuV clade have AC4 proteins with 130 aa (BLCrV: YP_009666510.1; Wissadula yellow mosaic virus: AOT83446.1; Abutilon golden mosaic Yucatan virus: YP_009506373.1).…”
Section: Genomic Characterization Of Cucumber Leaf Curl Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…All the proteins have the average size of BGVs proteins, with the exception of AC4. The AC4 protein is 130 aa in length, which is unusually long since the average size of AC4 protein is~85 aa for typical BGVs and 121 aa in length for BGVs belonging to SLCuV clade (Torres-Herrera et al, 2019). A BLASTP search revealed that only CuChLV and another three BGVs of the SLCuV clade have AC4 proteins with 130 aa (BLCrV: YP_009666510.1; Wissadula yellow mosaic virus: AOT83446.1; Abutilon golden mosaic Yucatan virus: YP_009506373.1).…”
Section: Genomic Characterization Of Cucumber Leaf Curl Virusmentioning
confidence: 99%
“…New World BGVs are grouped in several secondary linages or "clades," such as the Squash leaf curl virus (SLCuV) clade, the Abutilon mosaic virus (AbMV) clade and the Brazil clade (Argüello-Astorga et al, 1994;Rojas et al, 2005). Members of the SLCuV clade display distinctive features in their replication origin, AC4 protein and N-terminal domain of their Rep protein (Argüello-Astorga et al, 1994;Gregorio-Jorge et al, 2010;Torres-Herrera et al, 2019). Legumoviruses and sweepoviruses are grouped by the host that they specifically infect.…”
Section: Introductionmentioning
confidence: 99%
“…Monopartite BGVs encode six proteins, viz. C1/Rep, C2/TrAP, C3/REn, C4, V2, and V1/CP [ 9 ]. Homologs are encoded in one of the genomic components of bipartite BGVs, firstly DNA A (in this case, termed AC1/Rep, AC2/TrAP, AC3/REn, AC4, AV2, and AV1/CP); secondly, DNA B (the additional component in bipartite species) encodes two additional proteins: the nuclear shuttle protein (NSP) and the movement protein (MP).…”
Section: Introductionmentioning
confidence: 99%
“…The NW BGVs (~140 species) have a bipartite genome (DNA-A and DNA-B) with a few reported exceptions, while the OW BGVs include both bipartite and monopartite species, with a predominance of the latter (ca. 85%) [ 9 ]. A key difference between the New World (NW) and Old World (OW) BGVs is that the latter has an extra small open reading frame (ORF) that leads and moderately overlaps the CP gene, termed AV2/V2 or “precoat” gene [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[41]. Moreover, these malvaceous weeds are commonly infected by begomoviruses and develop striking golden/yellow mosaic symptoms [25,33,34,36,[42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%